EVALUASI PERALIHAN E-KATALOG 5.0 KE 6.0 PADA LPSE SEKRETARIAT DAERAH PROVINSI JAWA TIMUR - Emilia Zahra; Lutfiatu Khumairoh; Gusti Kanjeng Ratu (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to evaluate the transition of the E-Catalog system from version 5.0 to 6.0 at the LPSE of the Bureau of Goods/Services Procurement, Regional Secretariat of East Java Province, using the CIPP (Context, Input, Process, Product) evaluation model. The transition is expected to improve efficiency, transparency, and accountability in the procurement process. However, several challenges were identified, such as insufficient socialization, limited system readiness, and human resource constraints. This research employed a qualitative approach with in-depth interviews and observations involving relevant stakeholders. The evaluation results indicate that although version 6.0 offers positive potential, such as digital integration and enhanced transparency, the transition has not been fully optimal. This is evidenced by the large number of user complaints due to a lack of knowledge or preparedness in adapting to the new system. Therefore, improved communication, adequate infrastructure provision, and intensive assistance are required to ensure the successful and equitable implementation of the E-Catalog system version 6.0.